Overexpression of TRIM44 is related to invasive potential and malignant outcomes in esophageal squamous cell carcinoma - Tsutomu Kawaguchi; Shuhei Komatsu; Daisuke Ichikawa; Shoji Hirajima; Yukihisa Nishimura; Hirotaka Konishi; Atsushi Shiozaki; Hitoshi Fujiwara; Kazuma Okamoto; Hitoshi Tsuda; Eigo Otsuji (Tumor Biology)
Recent studies have shown that some members of the tripartite motif-containing protein family function as important regulators for carcinogenesis. In this study, we investigated whether tripartite motif-containing protein 44 acts as a cancer-promoting gene through its overexpression in esophageal squamous cell carcinoma. We analyzed esophageal squamous cell carcinoma cell lines to evaluate malignant potential and also analyzed 68 primary tumors to evaluate clinical relevance of tripartite motif-containing protein 44 protein in esophageal squamous cell carcinoma patients. Expression of the tripartite motif-containing protein 44 protein was detected in esophageal squamous cell carcinoma cell lines (8/14 cell lines; 57%) and primary tumor samples of esophageal squamous cell carcinoma (39/68 cases; 57%). Knockdown of tripartite motif-containing protein 44 expression in esophageal squamous cell carcinoma cells using several specific small interfering RNAs inhibited cell migration and invasion, but not cell proliferation. Immunohistochemical analysis demonstrated that the overexpression of the tripartite motif-containing protein 44 protein in the tumor infiltrated region was associated with the status of lymph node metastasis ( p = 0.049), and the overall survival rates were significantly worse among patients with tripartite motif-containing protein 44–overexpressing tumors than those with non-expressing tumors ( p = 0.029). Moreover, multivariate Cox regression model identified that overexpression of the tripartite motif-containing protein 44 protein was an independent worse prognostic factor (hazard ratio = 2.815; p = 0.041), as well as lymphatic invasion (hazard ratio = 2.735; p = 0.037). These results suggest that tripartite motif-containing protein 44 protein could play a crucial role in tumor invasion through its overexpression and highlight its usefulness as a predictor and potential therapeutic target in esophageal squamous cell carcinoma.